Penyuluhan Kesehatan dalam Menguatkan Kesehatan Masyarakat Dusun Rebobong Lor - Syaifurrahman, Arif; Zhafirah, Nabila Novta; Andina, Nova; Rivaldi, Fajar; Septiyanto, Aldi; Diana, Koni; Srinarari, Ardiningrum; Zulfikar, Fikri; Afiq, Faiz Fahmi; Anggreini, Eka Restu; Hilman, Oryzati (Universitas Muhammadiyah Yogyakarta, 2025)
Rebobong Lor Hamlet has a relatively high prevalence of Non-Communicable Diseases (NCDs), such as hypertension, diabetes, and gout. Environmental factors, including a high smoking rate and a sedentary lifestyle, are the primary contributors to these health problems. Economic limitations often become barriers to raising awareness about the importance of health. Rebobong Lor faces serious challenges in health education, as there is currently no well-organized system in place. The lack of public awareness regarding proper health practices further worsens the situation. Therefore, health education has become an urgent need to support overall community well-being. This community service program serves as a practical implementation of the theoretical knowledge gained by students during their academic studies. In this program, health was chosen as the central theme by the entire community service team. The health education initiative aimed to improve public awareness and knowledge of various health-related issues. The methods used in this outreach included the delivery of educational materials supported by various learning media, such as laptops, sound systems, digital presentations (PowerPoint), and posters. Evaluation results showed an increase in health knowledge among the residents of Rebobong Lor Hamlet following the education sessions on NCDs, particularly hypertension and diabetes mellitus.